Loss of H3K27me3 expression in canine nerve sheath tumors - Tekavec, Kristina; Švara, Tanja; Knific, Tanja; Mlakar, Jernej; Gombač, Mitja; Cantile, Carlo (Frontiers in Veterinary Science, 2022)
Nerve sheath tumors (NSTs) are characterized by neoplastic proliferation of Schwann cells, perineurial cells, endoneurial and/or epineurial fibroblasts. Diagnosis of NST is often challenging, particularly in distinguishing malignant NST (MNST) from other soft tissue sarcomas, or sometimes between low-grade MNST and benign NST. Recent studies in human pathology have demonstrated loss of trimethylation at lysine 27 of histone 3 (H3K27me3) in a subset of MNSTs using immunohistochemistry. Loss of H3K27me3 expression is rare in other high-grade sarcomas and also appears to be useful in distinguishing benign and low-grade MNSTs from high-grade subsets. In our retrospective study, we performed H3K27me3 immunohistochemistry in 68 canine tumors previously diagnosed as NST. We detected loss of H3K27me3 expression in 25% (n=17) of all canine NST, including one neurofibroma, whereas 49% (n=33) of tumors had mosaic loss of expression and 26% (n=18) retained expression. No statistically significant differences were found between H3K27me3 expression, histopathological features of tumors, and their immunoreactivity for Sox10, claudin-1, GFAP, and Ki67. Because the classification of canine NST is not yet fully established and its correlation with the prognosis and clinical course of the disease is lacking, prospective studies with possible genetic analyses are needed to assess the true diagnostic value of H3K27me3 loss in canine NST.